2021
DOI: 10.21608/ejchem.2021.67501.3459
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of dark and photoreactions on the removal and photo-decolorization of azo carmosine dye (E122) as food dye using Rutile- TiO2 suspension

Abstract: Dark and photoreactions have been employed to handle the various hazardous organic water contaminants as Synergistic technologies. The removal (dark reaction) and the photo-decolorization ( photoreaction) of azo carmosine dye (E122) as a food dye in an aqueous solution using Rutile-TiO2 and UV-A light were investigated in this work. Various parameters such as oxidant agents and temperature were determined. In dark reaction, the adsorption capacity and percentage of carmoisine dye removal elevated with the depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Though the design and synthesis of nanoscale materials with controllable qualities is a continuous difficulty in the area of nanoscience and nanotechnology, however, it remains important materials, that have good electrical, optical, and physical characteristics [7]. The use of nanotechnology in wastewater treatment that is produced by scientific labs or industry can make the wastewater treatment is better [8][9][10][11][12]. Spinel CoCr2O4 nanomaterial is a distinctive material that has a low bandgap, used as a pigment to colorant of ceramic, porcelain, plastic, and solar absorber coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Though the design and synthesis of nanoscale materials with controllable qualities is a continuous difficulty in the area of nanoscience and nanotechnology, however, it remains important materials, that have good electrical, optical, and physical characteristics [7]. The use of nanotechnology in wastewater treatment that is produced by scientific labs or industry can make the wastewater treatment is better [8][9][10][11][12]. Spinel CoCr2O4 nanomaterial is a distinctive material that has a low bandgap, used as a pigment to colorant of ceramic, porcelain, plastic, and solar absorber coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The negative value of ΔS 0 indicated that the photocatalytic decolorization of DB-22 was less random and the transition state formed in the degradation process had a lower structural freedom compared to the reactants, and this also confirms that the process was irreversible. 37,38 The lowest absolute values of E a , ΔH 0 , and ΔS 0 found for the catalyst used in the study are indicative of its highest catalytic activity. According to the literature, the value of the activation energy determines whether the reaction is diffusion or reaction rate controlled.…”
Section: Kinetic and Thermodynamic Studiesmentioning
confidence: 85%
“…These species are altered in potential power to decolorize and disintegrate any organic colored materials. Hydroxyl radical is a more active species in an aqueous solution with 2.8 V, hence it acts as a powerful oxidant to attack the dye molecules [53][54][55][56][57][58][59][60]. The suggested chlorazol black BH decolorization was displayed in figure.12 that mention in reference [17].…”
Section: E Suggested Mechanismmentioning
confidence: 99%